The effect of screening on melanoma incidence and biopsy rates. (28th June 2022) - Whiteman, David C.; Olsen, Catherine M.; MacGregor, Stuart; Law, Matthew H.; Thompson, Bridie; Dusingize, Jean Claude; Green, Adele C.; Neale, Rachel E.; Pandeya, Nirmala
Abstract: Background: Cutaneous melanomas are common cancers in white‐skinned populations, and early detection is promoted as a means of reducing morbidity and mortality. There is concern that increased skin screening is leading to overdiagnosis of indolent melanomas with low risk of lethality. The extent of melanoma overdiagnosis associated with screening is unknown. Objectives: To estimate possible overdiagnosis by comparing subsequent melanoma incidence and biopsy rates among people subjected to skin screening those who were not. Methods: We recruited 43 762 residents of Queensland, Australia, aged 40–69 years, with no prior history of melanoma, selected at random from a population register in 2010. At baseline, participants completed a comprehensive melanoma risk factor survey and were asked if their skin had been examined by a doctor in the 3 years prior to baseline. We calculated incidence and relative risk of histologically confirmed melanoma (invasive and in situ ) in years 2–7 of follow‐up, obtained through linkage to the cancer registry. In secondary analyses, we measured biopsy rates in years 2–6 of follow‐up. We used propensity score analysis to calculate adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs). Results: In total, 28 155 participants underwent skin screening prior to baseline. We observed 967 first‐incident melanomas (381 invasive) during 197 191 person‐years of follow‐up. Those screened had higher rates of melanoma (aHR 1·29, 95% CI 1·02–1·63) and subsequent skin biopses (aHR 1·85, 95% CI 1·69–2·04) than unscreened participants. The higher risk associated with skin screening was evident for in situ melanoma (aHR 1·45, 95% CI 1·09–1·92) but not invasive melanoma (aHR 1·05, 95% CI 0·72–1·54). In secondary analyses, where screening was defined as having a skin biopsy in the first year after baseline, we observed significantly increased risks of melanoma (aHR 1·53, 95% CI 1·23–1·89) and subsequent biopsies (aHR 2·64, 95% CI 2·46–2·84) relative to those who did not have a biopsy. Conclusions: People who undergo skin screening subsequently experience higher rates of biopsies and melanoma (especially in situ melanoma), even after adjusting for all known risk factors, consistent with overdiagnosis. What is already known about this topic? Cutaneous melanomas are common cancers in white‐skinned populations for which early detection is promoted as a means of reducing morbidity and mortality. There is concern that increased surveillance is leading to the overdiagnosis of indolent melanomas that are not destined to be lethal. The extent of melanoma overdiagnosis associated with surveillance is not known. What does this study add? People subjected to skin examinations by a doctor or who undergo skin biopsies subsequently have higher numbers of biopsies and higher rates of melanoma than people not subjected to either, even after adjusting for all known risk factors. These findings suggest that heightened surveillance leads to a proportion of melanomas being diagnosed that otherwise may not have come to clinical attention. Abstract : Melanoma is a common cancer, for which skin examinations are promoted as an early detection tool. In a large, prospective cohort, we documented the incidence of melanoma among people who had and had not been screened. Melanoma incidence was about 29% higher in the screened group over more than 5 years of follow‐up, suggesting possible overdiagnosis among people undergoing skin examinations. Linked Comment: K.J.L. Bell and T. Nijsten. Br J Dermatol 2022; 187:459–460 . Plain language summary available online